We Walk Alone - Aldrich, Ann, 1927 May 27- (Book collections on Project MUSE., 2006)
In 1955, this groundbreaking pulp revealed "underground" lesbian life in Greenwich Village. Part Kinsey-esque portraits of real people, part you-are-there reports on the scene in bars and offices and at clubs and house parties, this is an authentic "cultural artifact" of a resilient community on the cusp of change